A High‐Efficiency MRI Contrast Agent as well as a Tumor Therapeutic Agent. (28th November 2022) - Zhang, Nan; Meng, Lin; Wang, Lu; Zhang, Butian; Sun, Hongchen; Zhang, Kai
Abstract: Inorganic/polymercore/shell nanoparticles (NPs) for theranostics have always attracted research interest due to their flexible composition and facile synthesis. Here, core/shell NPs are prepared with gadolinium hydroxide nanorods cores and Mn ion‐doped polydopamine shells. After PEG modification, the relaxation rate of Gd(OH)3 @MnPDA‐PEG NRs achieved 35 s −1 mm −1 . The characterization results indicate that the predoping Mn ions obviously promote the effect of MRI compared with the nanorods without or with postdoping Mn ions, and the predoping method can effectively control the actual doping account of metal ions. Considering the toxicity, dopamine and manganese in molar ratio of 8:1 is finally chosen. Gd(OH)3 @MnPDA‐PEG nanorods are conducted in vivo and in vitro imaging and therapeutic experiments. The results show that the nanorods has low biological toxicity, excellent magnetic resonance imaging effects, clear photoacoustic imaging, and photothermal therapy effects. Abstract : Gd(OH)3 @MnPDA NRs are synthetized via predoping method that can effectively control the actual doping account of Mn ions. The special morphology of gadolinium hydroxide nanorods may enhance tumor uptakerate than spherical nanoparticles. The effect of magnetic resonance imaging of the nanorods has promoted obviously after doping Mn 2+, and achieved 35 s −1 mm −1 .